2011
DOI: 10.1161/circulationaha.111.034512
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role for the Protein Apoptosis Repressor With Caspase Recruitment Domain in Hypoxia-Induced Pulmonary Hypertension

Abstract: Background Pulmonary hypertension (PH) is a lethal syndrome associated with the pathogenic remodeling of the pulmonary vasculature and the emergence of apoptosis-resistant cells. ARC (Apoptosis Repressor with Caspase Recruitment Domain) is an inhibitor of multiple forms of cell death known to be abundantly expressed in striated muscle. We show for the first time that ARC is expressed in arterial smooth muscle cells of the pulmonary vasculature and is markedly up-regulated in several experimental models of PH. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 51 publications
(60 reference statements)
1
26
1
Order By: Relevance
“…Unlike our observations in a variety of human cancer cell types, hypoxia treatment of rat H9C2 cardiomyocytes and ventricular myocytes led to decreased ARC levels in a manner that correlated with the induction of apoptosis and/or necrosis (41). On the other hand, in the recent report by Zaiman et al, ARC was shown to be induced by hypoxia in isolated rat pulmonary arterial smooth muscle cells (44). Interestingly, the putative HIF1␣ binding site identified in our study appears to be conserved in primates but is not present in the mouse or rat ARC promoter (Fig.…”
Section: Discussioncontrasting
confidence: 90%
“…Unlike our observations in a variety of human cancer cell types, hypoxia treatment of rat H9C2 cardiomyocytes and ventricular myocytes led to decreased ARC levels in a manner that correlated with the induction of apoptosis and/or necrosis (41). On the other hand, in the recent report by Zaiman et al, ARC was shown to be induced by hypoxia in isolated rat pulmonary arterial smooth muscle cells (44). Interestingly, the putative HIF1␣ binding site identified in our study appears to be conserved in primates but is not present in the mouse or rat ARC promoter (Fig.…”
Section: Discussioncontrasting
confidence: 90%
“…2E). This proliferation function of ARC has not been previously described, although we have recently observed that ARC knockdown/knockout also impairs the proliferation of benign MCF-10A breast epithelial cells (unpublished data, C. Medina-Ramirez and R. Kitsis) and hypoxic pulmonary arterial smooth muscle cells in vivo (27). The mechanism of ARC-induced cellular proliferation is not known.…”
Section: Discussionmentioning
confidence: 53%
“…We generated mice with generalized deletion both alleles of nol3 (encompassing the entire open reading frame of ARC) and backcrossed them onto a C57Bl/6 background as described (27). The absence of ARC protein in hearts of nol3 −/− mice is shown in Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…55 ARC expression was initially believed to be limited to cardiac and skeletal myocytes and neurons, but recent data shows that is also induced at high levels in cancer cells 56-58 and hypoxic pulmonary artery smooth muscle cells in vivo . 59 …”
Section: Mechanisms Of Cell Deathmentioning
confidence: 99%